ANALYSIS OF IMMUNIZATION COVERAGE AND INSIGHTS INTO VACCINE ACCEPTANCE IN PARENTS OF CHILDREN AFFECTED WITH CHRONIC DISEASES (FOCUS ON ONCOLOGICAL AND NEUROLOGICAL PATIENTS) - Khalimzhanova, Shakhnoza (Nazarbayev University School of Medicine, 2024)
Objectives: Although vaccination can be considered as one of the most successful public health interventions to prevent infectious diseases, there are many people who remain vaccine hesitant. Children affected with chronic diseases have increased risk of infectious disease complications compared to healthy children, therefore their vaccine coverage should be optimal. Our aim was to measure vaccination coverage among children with chronic diseases admitted to NRCMCH pediatric Neurology and Oncology departments. Also, we aimed to study parental beliefs and determinants of vaccine hesitancy among parents. Methods: This prospective cross-sectional paper-based study was conducted between April 2022 to July 2023. Results: Overall, 59 participants were recruited to participate in our study to answer the paper-based questionnaire about their demographic information, their child’s vaccine coverage and their attitude towards vaccination. All the participants were 100% were female participants and the highest percentage of parents (45.8%) were between the ages 30-39. We found out that vaccination coverage in two departments was similar with a mean score of 0.81 and 0.77 in Neurology and Oncology, respectively. However, parents in neurology department were more vaccine hesitant compared to parents in oncology department with a mean score of 2.9 and 3.35 in Neurology and Oncology respectively.
Keywords: type of access: gated access